Relationship between the Management Accounting Information Usage, Market Orientation and Performance: Evidence from Vietnamese Tourism Firms - Do Huyen Trang; Le Mong Huyen; Luong Thi Thuy Diem; Tran Thi Quanh (My University, 2020)
Relationship between the Management Accounting Information Usage, Market Orientation and Performance: Evidence from Vietnamese Tourism Firms
Keywords: Market orientation; Tourism firms; Accounting usage